2009
DOI: 10.1021/ac900826u
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Dissolution of Thin Films of Cerium Oxide by Using a GaPO4 Crystal Microbalance

Abstract: In this study, microbalance measurements with a GaPO(4) crystal were performed to determine the dissolution rate of cerium oxide thin films at room temperature after a high temperature treatment of the hydroxide precursor Ce(OH)(4) at 700 degrees C. The properties of the GaPO(4) crystal enables gravimetric measurements to be performed after being heated at high temperatures where the classical quartz crystal microbalance irreversibly loses all its piezoelectric properties. The GaPO(4) resonators were calibrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Therefore, the dissolution of Ce 3+ is more dominant than Ce 4+ on the GDC particles. The reaction of CeO 2 dissolution can be estimated as follows,CeO2normals+3normalH++1/2H2normalO2Ce3++2normalH2O+1/2normalO2normalΔrnormalG=-125.9kJmol-1…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the dissolution of Ce 3+ is more dominant than Ce 4+ on the GDC particles. The reaction of CeO 2 dissolution can be estimated as follows,CeO2normals+3normalH++1/2H2normalO2Ce3++2normalH2O+1/2normalO2normalΔrnormalG=-125.9kJmol-1…”
Section: Discussionmentioning
confidence: 99%
“…In the case of CeO 2 , the dissolution rate is very slow in acids such as nitric acid and sulfuric acid regardless of the high concentration and elevated temperature utilized . The CeO 2 particles are dissolved either by the addition of a reducing agent such as Fe(II) and hydrogen peroxide (H 2 O 2 ) or by inducing oxygen vacancies by annealing in a reducing atmosphere . Jakab et al reported that the mixture of nitric acid (HNO 3 ) and H 2 O 2 significantly increases the dissolution speed of CeO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dissolution of CeO 2 with acid is shown as Eqs. 9 and 10 [45]. The dissolution of CeO 2 with acid is thermodynamically unfeasible, so CeO 2 is difficult to directly dissolve by HNO 3 .…”
Section: Heat Treatment and Nitrate Conversionmentioning
confidence: 99%
“…The dissolution of CeO 2 with acid is thermodynamically unfeasible, so CeO 2 is difficult to directly dissolve by HNO 3 . Often, a reducing reagent, such as H 2 O 2 , is added to reduce Ce 4+ to Ce 3+ and to facilitate the dissolution of CeO 2 with acid [45]. UO 2 is thermodynamically easily dissolved in HNO 3 [46].…”
Section: Heat Treatment and Nitrate Conversionmentioning
confidence: 99%